2015
DOI: 10.1111/jocn.12768
|View full text |Cite
|
Sign up to set email alerts
|

Improving self‐perception and self‐efficacy in patients with spinal cord injury: the efficacy of DVD‐based instructions

Abstract: Our study results confirmed that the spinal cord injury home rehabilitation DVD is a practical health education tool. We plan to use the proposed DVD intervention with a larger number of hospitalised patients, and to continuously monitor their improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
1
5
0
1
Order By: Relevance
“…In addition, the level of self-efficacy was significantly different between the two groups following the intervention in post-test and follow-up periods. In a research conducted by Chen et al on improving self-efficacy in patients with SCI -the efficacy of DVD-based instructions-, the results showed that multimedia DVD intervention has a positive impact on the selfcare intervention of the intervention group, which was consistent with our findings (27). In other research by Chen et al conducted on adult patients with asthma, selfefficacy improvements showed significantly higher selfcare behaviors with no interventions, which was consistent with our findings (28).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the level of self-efficacy was significantly different between the two groups following the intervention in post-test and follow-up periods. In a research conducted by Chen et al on improving self-efficacy in patients with SCI -the efficacy of DVD-based instructions-, the results showed that multimedia DVD intervention has a positive impact on the selfcare intervention of the intervention group, which was consistent with our findings (27). In other research by Chen et al conducted on adult patients with asthma, selfefficacy improvements showed significantly higher selfcare behaviors with no interventions, which was consistent with our findings (28).…”
Section: Discussionsupporting
confidence: 91%
“…A few studies have evaluated self-efficacy in patients with a spinal cord injury; however, these studies did not focus on preventing pressure ulcers. These studies reported that a nurse-coached exercise intervention (Sheehy, 2013) and home rehabilitation using a digital video disc (Chen, Wu, & Lin, 2015) were effective in improving self-efficacy in patients with a spinal cord injury. The findings from the present study might have been achieved because the self-efficacy enhancement program was designed using self-efficacy concepts based on Bandura's social cognitive theory (Bandura, 1986(Bandura, , 1991.…”
Section: Discussionmentioning
confidence: 99%
“…Early supported discharge (ESD) is a service that is suggested to be more effective after discharge following stroke. There are different ways to improve the patient’s self-confidence in, for example, postural balance-efficacy [ 21 23 ]. ESD might be a way to improve balance self-confidence.…”
Section: Introductionmentioning
confidence: 99%